A feasibility of simulation-based exercise programme for overweight adult in higher learning Institutions - Nik Yahya, Nik Siti Rahmah; Che Jamaludin, Farrah Ilyani; Firdaus, Mohd Khairul Zul Hasymi; Che Hasan, Muhammad Kamil (Elsevier, 2019)
Objective: This study was conducted to evaluate the feasibility of simulation-based exercise programme among overweight adult in higher learning institutes.